Extended Scalp Flaps for Extensive Soft Tissue Scalp Defects as a Day Surgery Procedure Under Local Anesthetic: A Single Centre Experience - Malahias, Marco; Ackling, Edward; Zubair, Omer; Harper, Natasha; Al-Rawi, Haytham; Khalil, Haitham (Journal of Neurological Surgery Part B: Skull Base, 2021)
Background Cutaneous malignancies are on the rise, associated with an increased number in scalp cancers that require wide local excision (WLE) to ensure clearance; the inelastic nature of the scalp poses a particular challenge when dealing with such large defects.Case presentation A series of 68 cases with large scalp defects following WLE for the clearance of squamous cell carcinoma, atypical fibroxanthoma, dermatofibrosarcoma protuberans, and melanoma skin cancers are presented. These cases were treated in one center under local anesthesia and underwent extended scalp flaps to close the resulting defect primarily without the use of skin grafts for the flap donor site on the scalp.Conclusion Extended scalp flap is a safe and reproducible solution for extensive scalp defects, which results in quicker wound healing with cosmetically superior results, and can be performed safely and comfortably under local anesthesia in the day case setting.
Keywords: scalp flap; skin cancers; head and neck cancer; cutaneous malignancy